Brimonidine tartrate 0.15% drops to reduce low post-LASIK residual myopia: A retrospective study. - Nir Gomel; Asaf Achiron; Nadav Shemesh; Elad Eilon; Tal Yahalomi; Dana Barequet; Nadav Levinger; Dafi Porat; Shmuel Levinger; Ami Hirsch; Nir Sorkin; Eliya Levinger (PLoS ONE)
Purpose Residual myopia following Laser-assisted in situ keratomileusis (LASIK) surgery poses a significant concern, with existing literature extensively detailing the use of timolol for treatment. This study aims to assess prediction factors for brimonidine tartrate 0.15% (Alphagan-P) response on post-LASIK residual myopic refraction reduction. Methods The study included consecutive patients who received Alphagan-P during their follow-up for post-LASIK residual myopia. Results We included 61 patients (55% male) with a mean age of 35.18 ± 10.13 Alphagan-P Treatment started at a mean of 4.94 ± 5.64 months after surgery for residual myopia of -0.53 ± 0.71D. Comparison analysis of patients who responded (n = 32, 51.6%) to patients who did not (n = 30, 48.4%) shows that responders were older (38.1 ± 9.1 vs. 32.3 ± 10.3, p = 0.03), had higher baseline myopic Spherical equivalent (SE, -0.82 ± 0.65 vs. -0.26 ± 0.66 p < 0.01), and lower uncorrected visual acuity (Uncorrected visual acuity [UCVA], 0.14 ± 0.2 vs. -0.003 ± 0.12 p = 0.01). Multiple Binary logistic regression confirmed these predictors for response (UCVA (OR=70.6, P = .006), larger SE (OR=3.8, P = .004,) and older age (OR=1.06, P = .03)). Conclusions Alphagan-P can reduce up to 0.5D of post-LASIK residual myopia in roughly 50% of subjects. This treatment might be recommended to fine-tune outcomes for low residual myopia.